NILAI-NILAI KARAKTER DALAM PEMBELAJARAN MATEMATIKA DI SD/MI - Siti Annisah (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2016)
The role of education in producing a quality generation, tough, and character should be maximized. The presence of shifting values or attitudes such as the reduced level of civility and adherence to students by teachers and parents habits, cheating, rapidly resolve problems when the desperate, a brawl between students and others indicated that there was a failure on the educational institutions in creating a human characteristic or Indonesia adopting noble. One of the factors that cause deterioration of character, attitude of learners is a system of education that only emphasizes on the formation of knowledge or intellectual, and less emphasis on the formation of the character/attitude of the students. It can be seen from the planning of learning, the process of teaching and learning activities, learning, and evaluation until the last national exam any more prioritize intellectual development alone. Therefore, there should be a change in the education system, in particular the activities of the learning process in schools, for example, by the integration of the values of the characters in the process of learning in each subject. Mathematics is a subject studied starting base level to the top level. This suggests that subjects mathematics provide knowledge and value in everyday life. The values of the character can be developed through several math learning activities in the classroom, as do the activities on monitoring and investigation to understand a material, mathematical concepts or rules for establishing the value of logical thinking, critical, creative, and innovative.